SOCIAL PEDAGOGICAL ASSISTANCE AT SCHOOL: PERFORMANCE ANALYSIS - Čižikienė, Janina; Virbalienė, Rita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
This article analyzes the peculiarities of the social pedagogical assistance at school. The purpose of social pedagogical assistance is defined in the education governing documents. These documents indicate that it is necessary to help the child to implement his right to education and to guarantee his safety at school. Thus,  effective social pedagogical assistance helps to solve the problems at school: the abuse of psychotropic substances, juvenile delinquency growth, increase of emotional and physical violence, dropping out of school. Effective aid can be achieved through teamwork principles, which require different areas of information, knowledge and skills. The article presents a review of scientific literature and research data which can be applied for improving of social pedagogical assistance at school in order to help students and families by involving various specialists. The study revealed essential factors that affect the social pedagogical assistance organization and real assistance to the student at school.